Covariance structure analysis of regional development data: an application to municipality development assessment - Kresimir Jurlin; Sanja Malekovic; Jaksa Puljiz; Dario Cziraky; Mario Polic (European Regional Science Association (ERSA), 2002)
This paper presents the results of the second phase of the project whose main objective is to provide an analytical basis for evaluating the level of development of the Croatian territorial units, i.e. municipalities in this particular case. In the second phase, a structural equation model with latent variables is estimated with the purpose to test the validity of the first (simple) model and its results. The structural model takes into account complex casual relations between simple and joint indicators (factors) used in the model, but its output is a single development level scale which allows interval ranking of the territorial units. On the other hand, the first model makes distinctions between municipalities according to each collective indicator (economic, structural and demogeographic), but it assumes that collective indicators are independent. As the intention from the beginning of the project was to try to categorise territorial units according to the methodology used by Structural Funds and based on NUTS classification, the first model was used for the final evaluation and categorisation of the territorial units, but it was somewhat changed according to the results of the structural equation model.
Keywords: 330